PERENCANAAN STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI MENGGUNAKAN SWOT DAN BSC PADA ENTREPRENEUR SORGUM - Nia Saurina; Endang Noerhartati; Marina Revitriani (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2023)
Since 2009, University of Wijaya Kusuma Surabaya (UWKS) has been involved in intensifying alternative food programs and importing food substitutions and driving entrepreneurship in sorghum commodities. Sorghum is the third food cereal crop after rice and maize. However, its use as food and industrial material is still limited, even decreasing with the availability of rice that meets needs at a relatively cheap price.The data used in this study include primary data and secondary data. Primary data obtained from interviews and observations conducted by interviewing 283 Sorghum Entrepreneurs who are members of 26 Sorghum Entrepreneurship Units (UES). SI and IT strategic planning for Sorghum Entrepreneurs in this study uses a ward and peppard framework with the SWOT and BSC methods.The results of the analysis that the sorghum industry is in quadrant 3 which supports turnaround is a business condition that is facing enormous opportunities, but also has some internal obstacles or weaknesses that must be faced, and improve the quality of service to customers by way of online service by presenting a system complete information and can meet customer needs so that the information is always up to date.Â